Optimizing Intelkam Unit Raising to Prevent Conflict Between Mass Organizations in the Jurisdiction of the Salatiga Police Region - Fahmi Arranirri (Advances in Police Science Research Journal, 2022)
Intelligence gathering is all efforts, work and activities carried out in a planned, directed manner by means of intelligence to create, create, change a condition in society so as to achieve favorable conditions for the main task of the police. In order to prevent conflicts between mass organizations, the Intelkam Unit as a preventive function can carry out fundraising aimed at influencing and or changing attitudes, behavior, opinions, emotions from certain targets which are carried out in a closed manner in order to create conditions that support the implementation of the main tasks of the National Police. Therefore, this research wants to explore how the competence of members of the Intelkam Unit in carrying out fundraising and how the implementation of raising by the Intelligence and Security Unit is to prevent conflicts between mass organizations in the Salatiga Police Legal Area. In this discussion, the researcher uses an analytical knife with competency theory, management theory, the concept of seven-step operational management, and the raising concept listed in Perkabik No. 3 of 2013 concerning Raising. This study uses a qualitative approach with the type of concept analysis research with the research location at the Salatiga Police Station. The results of this study indicate that the competence of members of the intelligence unit is still incompetent because it is influenced by members who have not carried out specialization development education then in the implementation of fundraising it is necessary to do a target analysis in order to obtain basic knowledge of the target. In addition, it was found that inadequate infrastructure facilities hindered the manufacture of intelligence products by the intelligence unit. Based on the research results, there are several conclusions that can be given to the Salatiga Police, namely the provision of unit training and seminars on science, procurement of intelligence facilities and infrastructure, and the use of applications to support member reporting to the leadership.